2022
DOI: 10.21037/atm-22-341
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lens opacity and axial length on concomitant screening of maculopathy by swept-source optical coherence tomography-based optical biometer

Abstract: Background Preoperative evaluation of macular disorders is crucial to predict postoperative visual outcomes among patients with cataract. The swept-source optical coherence tomography (SS-OCT) based optical biometer was proved to be useful in screening macular pathology, while the impact of lens opacities and axial lengths on macular disease screening using SS-OCT based optical biometer remained unknown. This study aimed to evaluate the influence of lens opacities and axial lengths on foveal image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Other studies have compared the diagnostic accuracy of currently available SS-OCT devices as done in our study [ 6 , 11 13 ]. These studies have similarly evaluated the diagnostic utility of biometric SS-OCT and have reported a sensitivity ranging from 46.0 to 81.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have compared the diagnostic accuracy of currently available SS-OCT devices as done in our study [ 6 , 11 13 ]. These studies have similarly evaluated the diagnostic utility of biometric SS-OCT and have reported a sensitivity ranging from 46.0 to 81.0%.…”
Section: Discussionmentioning
confidence: 99%